Surface Modification Inspired by Malayopython Reticulatus for Friction Control - Mohd Danial, Ibrahim; Alyssa Asong, Ananthan; Sunami, Yuta; Barroy, Pierre (2021)
This research is to study the frictional characteristics of a real Malayopython Reticulatus snake ventral scales and to evaluate its feasibility as an inspiration for surface modification designs. Two types of experiments were carried out at different sliding directions and surfaces to analyze the frictional characteristics of snake ventral scales. From this study, snakeskin demonstrates frictional anisotropy and it is prominent under wet condition. Based on these findings, surface designs inspired by snakeskin is suitable for parts or components that are subjected to directional friction especially in wet conditions.